COSINE ERROR REDUCTION ON THE UNIVERSAL MEASURING MACHINE CALIBRATION USING DISPLACEMENT LASER INTERFEROMETER - Ardi Rahman (Widyariset, 2012)
The calibration is important for many people as it can guarantee the traceability of measurement. Universalmeasuring machine is one of the coordinate measuring machine which is capable to calibrate the amount ofdimensional measurement standards, while, the UMM was calibrated by displacement laser interferometer. Inthe UMM calibration, cosine error was occurred, where the measurement result value is greater than the actualdimension value. The aim of this research was to reduce the cosine error in the UMM calibration using the DLIby adjusting the DLI optics. The results showed that the cosine error was decreased 10 μm compared to the 2006calibration data, and the uncertainty of measurement decrease of 61.5%.